Production method for preparing silicon-aluminum alloy from coal gangue and fly ash
By preparing coal gangue and fly ash into high-melting point silicon-aluminum alloys and using negative pressure vacuum casting method, the problems of poor high temperature and corrosion resistance of silicon-aluminum alloys in the prior art are solved, and efficient resource utilization and performance improvement of materials are achieved.
Patent Information
- Application Number
- CN202510068478.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-08
AI Technical Summary
In the prior art, when preparing silicon-aluminum alloys, there are problems with poor high temperature resistance and corrosion resistance.
Coal gangue and fly ash are used as raw materials, and silicon-aluminum alloys with high melting point and stable properties are prepared through grinding, mixing, granulation, fabric and belt-type pre-reduction processes, and their density and corrosion resistance are further improved through negative pressure vacuum casting.
It has achieved the high temperature stability and corrosion resistance of silicon-aluminum alloys, reduced production costs, and effectively solved the accumulation of industrial solid waste, and met the requirements of green and sustainable development.
Smart Images

Figure CN119776665A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum alloys, and in particular to a production method for preparing silicon aluminum alloy by utilizing coal gangue and fly ash. Background Art
[0002] Gangue and fly ash are the main industrial solid wastes generated by the coal, power and other industries, which contain rich resources. Therefore, it is urgent to carry out deep processing of gangue and fly ash to turn waste into treasure and ensure the secondary value-added of resources; at the same time, it is an important measure to strengthen environmental protection and promote resource recycling.
[0003] Chinese patent CN115044809B discloses a cast aluminum silicon alloy and its preparation method and an aluminum silicon alloy for aviation or automobile castings. The invention uses aluminum ingots with a purity of 99.00-99.77% as raw materials. The secondary dendrite arm spacing of the cast aluminum silicon alloy is small, which can improve the room temperature strength; but the Ti added in the invention B2 Elements such as Sr tend to form strengthening phases with large potential differences in the matrix. These strengthening phases are prone to electrochemical reactions in corrosive environments, thereby exacerbating pitting corrosion.
[0004] Chinese patent CN109487129B discloses an ultra-high performance silicon aluminum alloy and its preparation method. By adjusting the ratio of silicon aluminum alloy elements and improving the method, the prepared new silicon aluminum alloy has higher tensile strength and higher hardness. In the invention, the amount of iron added is 5.5-6.5%. Although it can improve the hardness of the alloy under high temperature conditions, the high iron content is prone to increase the low melting point eutectic phase, which is prone to local melting and cracking at high temperatures, affecting the mechanical properties and high temperature resistance of the alloy material.
[0005] At present, the silicon aluminum alloy prepared by the production method of the existing technology still has the problem of poor high temperature resistance and corrosion resistance.
[0006] Therefore, a production method for preparing silicon aluminum alloy by using coal gangue and fly ash is proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a production method for preparing silicon aluminum alloy using coal gangue and fly ash. First, using coal gangue and fly ash as raw materials can solve the problem of waste accumulation and realize resource utilization; it contains a large amount of active silicon and aluminum components, which can reduce costs; secondary mixing and humidification of charcoal powder and distilled water can also improve the molding performance, and the prepared silicon aluminum alloy has a high melting point and strong high temperature resistance. Secondly, the granulation and distribution system promotes uniform heat transfer, uniform particles make sintering smooth and reduce cracks, and uniform distribution makes the structure tight, which improves the high temperature resistance of silicon aluminum alloy. Furthermore, the belt pre-reduction process removes impurities such as sulfur and phosphorus, and improves the density and uniformity of the alloy material; the slag-making agent can remove impurities and reduce energy consumption; negative pressure vacuum casting discharges gas, reduces oxidation, and improves the density and corrosion resistance of silicon aluminum alloy.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] The present invention provides a production method for preparing silicon aluminum alloy by using coal gangue and fly ash. The production method is as follows:
[0010] Mixing coal gangue powder and fly ash powder to obtain mixture A; and then fully mixing mixture A with wet charcoal powder to obtain mixture B;
[0011] The mixture B is granulated to obtain a material; the material is fed into a distribution system to be evenly distributed to obtain a block material;
[0012] The block material and the reducing agent are subjected to a heating and impurity removal treatment on a belt pre-reducing machine to obtain material A; the material A is screened for a second time to obtain material B;
[0013] The material B is mixed with coal particles and then roasted at high temperature to obtain liquid silicon-aluminum alloy; the liquid silicon-aluminum alloy is allowed to stand for cooling, subjected to negative pressure vacuum casting, shaping, cooling, demoulding, cutting, cleaning and correction, and fine processing to obtain the silicon-aluminum alloy.
[0014] Preferably, the production method of mixture A is: respectively grinding coal gangue, fly ash and charcoal with a Raymond mill to a particle size of 80-100 mesh to obtain coal gangue powder (CGP), fly ash powder (FAP) and charcoal powder (CP); feeding coal gangue powder (CGP) and fly ash powder (FAP) into a double-helix conical mixer at a mass ratio of 35-55:25-45, adjusting the speed of the double-helix conical mixer to 30-60r / min, mixing for 15min, controlling the material filling rate in the double-helix conical mixer to 70%, and performing a thorough mixing to obtain mixture A.
[0015] Preferably, the production method of mixture B is: 8-12 parts of charcoal powder (CP) and 3 parts of distilled water are pre-mixed to obtain wet charcoal powder, and mixture A, wet charcoal powder and 10 parts of distilled water are added to a spiral stirrer for secondary thorough mixing to obtain mixture B.
[0016] Preferably, the material production method is: sending the mixture B to a twin-screw extruder granulator with a pressure of 80-100 MPa and a feed rate of 10 kg / h and adding 5 parts of graphite lubricant to granulate the material; the particle size of the granulation of the twin-screw extruder granulator is controlled within the range of 3-5 mm.
[0017] Preferably, the block production method is: feed the material into the distribution system to make it evenly distributed to obtain the block; the distribution system adopts a shuttle distributor, the running speed of the shuttle distributor is 3m / min, the end point residence time is 10s, and the material flow rate is 10-15m 3 / h, the height between the discharge port and the fabric plane is 1.0m.
[0018] Preferably, the production method of material A is as follows: the block material is gradually heated to 1150-1250°C on a belt pre-reducing machine and maintained at this temperature for 18-25 minutes; the air flow rate of the wind system is adjusted to 10m / s and the air flow rate is 20m 3 / min, so that the block material forms the material A with uniform thickness on the belt pre-reduction machine; the air flow direction of the wind system is opposite to the block material conveying direction.
[0019] Preferably, the production method of liquid silicon aluminum alloy is as follows: material A is screened twice through a vibrating circular screen to obtain material B; material B is mixed with coal particles in a mass ratio of 4:1 and sent to the silo of a silicon-aluminum-iron alloy furnace, and is calcined at a high temperature of 2100-2150°C for a sufficient reduction reaction, and liquid silicon aluminum alloy is obtained after calcination for 2.3-2.5 hours; the mesh aperture of the vibrating circular screen is 1.0 mm; and the moving speed of material A on the mesh is 0.2 m / s.
[0020] Preferably, the production method of silicon aluminum alloy is: liquid silicon aluminum alloy flows into a ladle, and 2 parts of slag-forming agent are added into the ladle to purify and remove impurities; the liquid silicon aluminum alloy is allowed to stand in the ladle for 13-15 minutes, and the temperature is reduced to 1450-1500°C and cast using a negative pressure vacuum pressure casting machine; after shaping, the alloy is cooled, demolded, and the surface is cleaned, the size is corrected, and the alloy is fine-processed to obtain the silicon aluminum alloy; wherein the slag-forming agent contains 80% NaCl and 20% Na3AlF6.
[0021] Preferably, the casting is as follows: placing the prefabricated mold into a vacuum pressure casting machine, controlling the negative pressure value of the vacuum pressure casting machine to stabilize at 170-180 hPa, and then pouring the liquid silicon aluminum alloy into the mold through a gate system and waiting for shaping.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. First, gangue and fly ash are solid wastes generated during coal mining and processing. Grinding, crushing and mixing them as raw materials for preparing silicon-aluminum alloy can effectively solve the problem of the accumulation of gangue and fly ash, realize the resource utilization of waste, and meet the requirements of green and sustainable development; secondly, gangue and fly ash contain a large amount of active silicon and aluminum components. Using these components to prepare silicon-aluminum alloy can greatly reduce production costs; thirdly, adding wet charcoal powder and distilled water during the secondary mixing process can make the wet charcoal powder better dispersed in the mixture and more fully contact with other raw materials; at the same time, it also helps to improve the molding properties of the raw materials, make the raw materials more evenly mixed in the belt pre-reducer, and the prepared silicon-aluminum alloy has stable performance, high melting point, and stable performance at high temperature.
[0024] 2. Through the dual effects of granulation and distribution system, heat is evenly transferred inside the material and the prepared particles are uniform. During high-temperature sintering, particles of uniform size can make the sintering reaction proceed more smoothly and reduce defects such as cracks caused by concentrated thermal stress. After uniform distribution, the internal structure of silicon-aluminum alloy becomes tighter and more stable. Under high temperature conditions, the tight structure can better resist the volume change caused by thermal expansion and reduce the internal stress caused by thermal expansion difference. At the same time, the lubricant graphite forms a protective film on the surface of silicon-aluminum alloy particles to prevent the surface of the material from contacting with oxidizing gases, reduce the occurrence of oxidation reactions, protect the internal structure of the material, maintain the stability of its performance, and help improve the high temperature resistance of silicon-aluminum alloy.
[0025] 3. The belt pre-reduction process gradually decomposes harmful impurities such as sulfur and phosphorus from the block material by heating and high-temperature insulation, and takes them away by regulating the wind system, significantly reducing the impurity content. Under high temperature conditions, charcoal powder is used as a reducing agent to pre-reduce silicon aluminum oxide. The removal of impurities makes the silicon aluminum alloy composition pure and the atomic arrangement more compact, thereby improving the material density and structural uniformity. The uniform block thickness ensures uniform heating through subsequent processes to avoid uneven density caused by composition differences or uneven porosity; the reduction of impurities improves the corrosion resistance of the alloy surface, which is manifested as a decrease in corrosion current and an increase in polarization resistance. At the same time, the grain boundary strength is enhanced, the internal stress distribution is more uniform, and the material's stress corrosion cracking resistance is improved; high-temperature roasting and appropriate material ratios promote atomic diffusion and defect filling, further improving density and corrosion resistance.
[0026] 4. The slag-making agent added in the belt pre-reduction process is composed of 80% NaCl and 20% Na3AlF6. The active substances such as fluoride ions produced by the decomposition of Na3AlF6 at high temperature can react with impurities to form stable compounds, thereby effectively removing impurities. The addition of NaCl and Na3AlF6 can also reduce the melting point of the liquid silicon aluminum alloy, so that it maintains good fluidity at a lower temperature, thereby reducing the casting temperature, reducing energy consumption and high-temperature damage to equipment. In addition, the lower casting temperature reduces the contact between the alloy and the air, reduces the oxidation rate, and improves the corrosion resistance of the alloy. The negative pressure vacuum casting method can discharge gas before the liquid alloy solidifies, reduce pore formation, and improve the density and quality of the casting. Under the negative pressure state, the oxidation and air entrainment of the liquid alloy during the filling process are reduced, the probability of surface oxidation is reduced, and the corrosion resistance is further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The process flow chart of preparing silicon aluminum alloy in the present invention. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] See also Figure 1 The present invention provides a production method for preparing silicon aluminum alloy by using coal gangue and fly ash, and the technical scheme is as follows:
[0030] The substance information involved in the present invention is as follows:
[0031] NaCl CAS: 7647-14-5; Na3AlF6 CAS: 13775-53-6;
[0032] Coal gangue and fly ash were selected from Huainan Mining Group Co., Ltd.; charcoal was selected from Jiangsu Qiu Lianjun Weibao Material Technology Co., Ltd.
[0033] Example 1
[0034] The gangue, fly ash and charcoal are ground respectively by Raymond mill to make the particle size of 80 meshes to obtain gangue powder, fly ash powder and charcoal powder; the gangue powder (CGP) and fly ash powder (FAP) are fed into a double-helix cone mixer at a mass ratio of 35:25, the speed of the double-helix cone mixer is adjusted to 30r / min, the mixing is carried out for 15min, the material filling rate in the double-helix cone mixer is controlled to 70%, and a full mixing is carried out to obtain a mixture A; 8 parts of charcoal powder (CP) and 3 parts of distilled water are pre-mixed to obtain wet charcoal powder, and the mixture A, the wet charcoal powder and 10 parts of distilled water are added into a spiral stirrer for humidification and a second full mixing is carried out to obtain a mixture B.
[0035] The mixture B was sent to a twin-screw extruder and granulated with 5 parts of graphite lubricant to obtain the material. The pressure of the twin-screw extruder was controlled to be 80 MPa, the feed rate was 10 kg / h, and the particle size was 3 mm. The material was sent to a shuttle distributor to be evenly distributed to obtain a block material. The running speed of the shuttle distributor was controlled to be 3 m / min, the end point residence time was 10 s, and the material flow rate was 10 m 3 / h, the height between the discharge port and the fabric plane is 1.0m.
[0036] The block material is gradually heated to 1150℃ on the belt pre-reduction machine and maintained for 19 minutes. Under high temperature, harmful impurities such as sulfur and phosphorus in the block material are gradually decomposed and separated out. The air flow speed of the wind system is adjusted to 10m / s, and the air flow direction of the wind system is opposite to the block material conveying direction. The air flow rate is 20m 3 / min, taking away harmful substances such as sulfur and phosphorus; making the block material form material A with uniform thickness on the belt pre-reduction machine.
[0037] Material A is screened twice by a vibrating circular screen to remove small particles and dust, thereby obtaining material B. The mesh size of the vibrating circular screen is 1.0 mm, and the moving speed of material A on the screen is 0.2 m / s.
[0038] Material B is mixed with coal particles in a mass ratio of 4:1 and sent to the silo of the silicon-aluminum-iron alloy furnace. After being calcined at 2100°C for a full reduction reaction, liquid silicon-aluminum alloy is obtained after calcining for 2.2 hours. At the same time, the high-temperature hot flue gas generated in the furnace is sent to a belt pre-reduction machine for recycling. The remaining part is subjected to smoke purification treatment and ultra-low emissions are carried out after meeting the emission standards.
[0039] Liquid silicon aluminum alloy is flowed into a ladle, and 2 portions of slag-forming agents are added into the ladle for purification and impurity removal; the liquid silicon aluminum alloy is allowed to stand in the ladle for 13-15 minutes, and the temperature is reduced to 1450-1500°C. A prefabricated mold is placed in a negative pressure vacuum box by a negative pressure vacuum casting method, and after the negative pressure value in the control box is stabilized at 170-180hpa, the liquid silicon aluminum alloy is poured into the mold through a gate system and waits for shaping; after shaping, the alloy is cooled, demoulded, and the surface is cleaned, the size is corrected, and fine-processed to obtain a silicon aluminum alloy; wherein the slag-forming agent contains 80% of NaCl and 20% of Na3AlF6.
[0040] Embodiment 2-10
[0041] The process flow and experimental method of Example 1 are referred to, but some parameters are changed, which are specifically summarized in Table 1.
[0042] Table 1 Process parameters adjusted in Examples 1-10
[0043]
[0044] Examples 11-20
[0045] The process flow and experimental method of Reference Example 9 were followed, but some parameters were changed, as specifically summarized in Table 2.
[0046] Table 2 Process parameters adjusted in Examples 11-20
[0047]
[0048]
[0049] In order to verify the necessity of some technical solutions in the present invention for achieving the technical effects of the present invention, some comparative examples of the present invention will be shown and described below.
[0050] Comparative Example 1
[0051] Different from Example 1, Comparative Example 1 did not use a Raymond mill for grinding, and did not add charcoal powder (CP), but directly mixed the ground coal gangue powder (CGP) and fly ash powder (FAP) according to the proportion of parts.
[0052] Comparative Example 2
[0053] Different from Example 1, Comparative Example 2 does not adopt a staged mixing method, but directly mixes the ground coal gangue powder (CGP), fly ash powder (FAP) and charcoal powder (CP) according to the mass proportion.
[0054] Comparative Example 3
[0055] Different from Example 1, Comparative Example 3 does not perform granulation treatment, and only simply mixes the mixture B with 5 parts of graphite lubricant before performing subsequent processes.
[0056] Comparative Example 4
[0057] Different from Example 1, in Comparative Example 4, the height between the material discharging port and the material discharging plane in the material discharging system is set to 2.5 m.
[0058] Comparative Example 5
[0059] Different from Example 9, in Comparative Example 5, the airflow direction of the wind system is perpendicular to the block material conveying direction.
[0060] Comparative Example 6
[0061] Different from Example 9, in Comparative Example 6, material B and coal particles are mixed in a mass ratio of 1:1 and calcined at high temperature to obtain liquid silicon-aluminum alloy.
[0062] Comparative Example 7
[0063] Different from Example 9, the slagging agent added in Comparative Example 7 is changed to calcium oxide, and other process parameters remain unchanged.
[0064] Comparative Example 8
[0065] Different from Example 9, Comparative Example 8 does not adopt negative pressure vacuum casting method, but adopts sand mold gravity casting method.
[0066] Experimental Example 1
[0067] The melting point of silicon aluminum alloy was determined by GB / T 40320-2021; the high temperature tensile strength and high temperature yield strength of silicon aluminum alloy were determined by FLGL high temperature material tensile testing machine of Fuller Instruments; the temperature of FLGL high temperature material tensile testing machine of Fuller Instruments was set to 300°C, and the high temperature tensile strength and high temperature yield strength of silicon aluminum alloy specimens were tested at 300°C; the test results are shown in Table 3.
[0068] Table 3 High temperature resistance of silicon aluminum alloys prepared in Examples 1-6 and Comparative Examples 1-2
[0069] Example Melting point / ℃ High temperature tensile strength / MPa High temperature yield strength / MPa Example 1 577 283.5 241.3 Example 2 579 287.8 245.7 Example 3 578 285.7 244.3 Example 4 637 298.2 248.4 Example 5 621 296.8 246.6 Example 6 578 285.1 243.8 Comparative Example 1 376 113.3 87.9 Comparative Example 2 432 150.8 100.3
[0070] As shown in the data of Table 3, the high temperature tensile strength and high temperature yield strength of Examples 1-6, Comparative Example 1 and Comparative Example 2 were tested at 300°C. The test results show that the melting points of the silicon aluminum alloys prepared in Examples 1-6 are all higher than 500°C, and the high temperature tensile strength and high temperature yield strength measured at 300°C are significantly higher than 200MPa, indicating that the prepared silicon aluminum alloy has good high temperature deformation resistance. Firstly, gangue and fly ash are solid wastes generated in the process of coal mining and processing. Grinding, crushing and mixing them as raw materials for preparing silicon-aluminum alloy can effectively solve the problem of the accumulation of gangue and fly ash, realize the resource utilization of waste, and meet the requirements of green and sustainable development; secondly, gangue and fly ash contain a large amount of active silicon and aluminum components. Using these components to prepare silicon-aluminum alloy can greatly reduce production costs; furthermore, adding wet charcoal powder and distilled water in the secondary mixing process can make the wet charcoal powder better dispersed in the mixture and more fully contact with other raw materials; at the same time, it also helps to improve the molding properties of the raw materials, make the raw materials more evenly mixed in the belt pre-reduction machine, and the prepared silicon-aluminum alloy has stable performance, high melting point, and stable performance under high temperature conditions. In Comparative Example 1, no Raymond mill was used for grinding and no charcoal powder (CP) was added, resulting in excessive particle size of the raw materials, which affected the mixing uniformity between the raw materials; in the subsequent smelting process, segregation occurred around the large particles of the raw materials, which could not be fully melted, and the tensile strength and yield strength of the obtained silicon aluminum alloy measured under high temperature conditions were quite different; charcoal powder played a reducing and loosening role in the preparation process of silicon aluminum alloy, which was beneficial to the transfer of heat inside the alloy material and promoted the uniformity of the reduction reaction, thereby improving the quality of the silicon aluminum alloy; the failure to add charcoal powder would result in the formation of coal gangue powder and fly ash powder. The oxide impurities generated during the reaction cannot be removed; the grains of the silicon-aluminum alloy become larger, reducing the purity of the silicon-aluminum alloy, thereby further affecting its high temperature resistance; while in Comparative Example 2, the segmented mixing method is not adopted, and the ground coal gangue powder (CGP), fly ash powder (FAP) and charcoal powder (CP) are directly mixed according to the mass fraction ratio, and the charcoal powder agglomerates. The agglomerated carbon powder is difficult to be evenly integrated into the alloy, resulting in a high local carbon content, forming a carbide aggregation area, reducing the toughness of the alloy, thereby reducing its tensile strength and yield strength at high temperature, causing its high temperature resistance to deteriorate.
[0071] Experimental Example 2
[0072] GB / T 40320-2021 was used to determine the melting point of silicon aluminum alloy; thermal expansion coefficient was determined using a thermal dilatometer;
[0073] The thermal stability mass loss rate was measured using a thermogravimetric analyzer; the thermal stability mass loss rate (W) was calculated using the following formula: The silicon-aluminum alloy begins to undergo oxidation reaction at 400°C, m1 represents the mass of the silicon-aluminum alloy before the reaction begins, and m2 represents the mass of the silicon-aluminum alloy after the oxidation reaction ends; the test results are shown in Table 4.
[0074] Table 4 High temperature resistance of silicon aluminum alloys prepared in Examples 7-10 and Comparative Examples 3-4
[0075] Example Melting point / ℃ Thermal expansion coefficient / (ppm / ℃) Thermal stability mass loss rate / % Example 7 584 10.2 0.56 Example 8 583 9.6 0.55 Example 9 643 7.8 0.35 Example 10 638 8.3 0.42 Comparative Example 3 407 24.1 23.7 Comparative Example 4 356 13.8 5.3
[0076] According to the test results of Table 4, it can be seen that the melting point, thermal expansion coefficient and thermal stability mass loss rate of Examples 7-10, Comparative Examples 3 and Comparative Examples 4 were tested. The test results show that the melting point of the silicon aluminum alloy prepared in Examples 7-10 is significantly higher than 500°C, and the higher the melting point, the lower the thermal expansion coefficient and thermal stability mass loss rate; this is because after the dual effects of granulation treatment and the distribution system, the heat is evenly transferred inside the material, and the prepared particles are uniform; during the high-temperature sintering process, particles of uniform size can make the sintering reaction more stable and reduce defects such as cracks caused by thermal stress concentration; after uniform distribution, the internal structure of the silicon aluminum alloy is more compact and stable. Under high temperature conditions, the compact structure can better resist the volume change caused by thermal expansion and reduce the internal stress caused by thermal expansion differences; at the same time, the lubricant graphite forms a protective film on the surface of the silicon aluminum alloy particles to prevent the surface of the material from contacting with oxidizing gases, reduce the occurrence of oxidation reactions, protect the internal structure of the material, maintain the stability of its performance, and help improve the high temperature resistance of the silicon aluminum alloy. In comparative example 3, no granulation treatment is performed, and only mixture B is simply mixed with 5 parts of graphite lubricant. The prepared silicon aluminum alloy is in irregular blocks, which is difficult to be evenly stacked and tightly arranged. The fluidity of the alloy is poor, which aggravates the reaction unevenness and inconsistent heat transfer, thereby affecting the progress and degree of reaction, reducing the quality of the alloy, causing its thermal expansion coefficient and thermal stability mass loss rate to increase, and reducing its high temperature resistance; in comparative example 4, the height of the discharge port and the distribution plane in the distribution system is set to 2.5m. In the process of the material falling from the discharge port, there is a more sufficient dispersion distance under the action of gravity, and the dispersion area in the horizontal direction is wider, so that the material distribution is more uniform; but at the same time, the impact force of the material reaching the distribution plane is significantly increased, causing the material to splash at the landing point, forming irregular accumulation around the landing point, reducing the overall flatness and uniformity of the alloy material; and it is easier to raise dust, causing material loss, which is not conducive to the subsequent process; the thermal expansion coefficient and thermal stability mass loss rate of the prepared silicon aluminum alloy increase, and its high temperature resistance is reduced.
[0077] Experimental Example 3
[0078] The density of silicon aluminum alloy is measured by KW-300A aluminum alloy density measuring instrument; the corrosion performance test of silicon aluminum alloy adopts salt spray test simulating marine environment; 2.5% sodium chloride solution is evenly sprayed on the surface of silicon aluminum alloy sample for 96 hours. After the experiment, the polarization resistance of silicon aluminum alloy sample is tested by CHI1200C portable electrochemical workstation; the stress corrosion cracking resistance of silicon aluminum alloy sample is tested by Sansi Zongheng UTM6503 electronic universal testing machine; the test results are shown in Table 5.
[0079] Table 5 Corrosion resistance of silicon aluminum alloys prepared in Examples 11-15 and Comparative Examples 5-6
[0080]
[0081] As can be seen from the data in Table 5, the density, polarization resistance and stress corrosion cracking resistance of Examples 11-15, Comparative Example 5 and Comparative Example 6 were tested. The test results show that the density of the silicon aluminum alloys prepared in Examples 11-15 is greater than 2.0 g / cm 3 , polarization resistance is greater than 1900Ω / cm 2, the stress corrosion cracking resistance is greater than 24.00MPa; this is because the block material is heated up in the belt pre-reduction machine and maintained for a certain period of time so that harmful impurities such as sulfur and phosphorus in the block material are gradually decomposed and separated, and the harmful substances such as sulfur and phosphorus are taken away by the wind system. The reducing agent charcoal powder in the block material pre-reduces the silicon aluminum oxide under the high temperature state of the belt pre-reduction machine; the reduction of impurities makes the composition in the alloy purer and the atomic arrangement more compact, which is beneficial to improve the density of silicon aluminum alloy; the alloy surface without impurity interference can better resist the adsorption and reaction of ions, so that the corrosion current is reduced and the polarization resistance is increased; the grain boundary strength is improved, and the stress distribution inside the material is more uniform, thereby enhancing the stress corrosion cracking resistance; adjustment The air flow velocity, direction and flow rate of the rectification system can effectively remove impurities, thereby forming a material A of uniform thickness. The uniform material thickness is conducive to uniform heating and reaction in subsequent processes, making the structure of the silicon-aluminum alloy more uniform during the formation process, avoiding the occurrence of uneven density due to local composition differences and uneven porosity, thereby improving the density, polarization resistance and stress corrosion cracking resistance of the silicon-aluminum alloy, and improving the corrosion resistance of the silicon-aluminum alloy; at the same time, the appropriate material ratio and high-temperature roasting environment can ensure that the reduction reaction is fully carried out inside the material, the diffusion rate of atoms is accelerated, and defects such as pores inside the alloy are filled, which helps to improve the density of the silicon-aluminum alloy, thereby improving its corrosion resistance. In Comparative Example 5, the airflow direction of the wind system is perpendicular to the block conveying direction, and the airflow cannot effectively carry away impurities from the mainstream of the block. The impurities adhere to the surface of the block, resulting in a high impurity content. The purity and density of the alloy material are greatly affected, and its polarization resistance and stress corrosion cracking resistance are greatly reduced, and the corrosion resistance is weakened; in Comparative Example 6, material B and coal particles are mixed in a mass ratio of 1:1 and calcined at high temperature to obtain liquid silicon-aluminum alloy, resulting in an excessively high carbon content in the material, forming too many carbide phases, and causing the alloy structure to be loose, thereby reducing the density and hardness of the alloy, reducing the bonding strength of the grain boundaries, and making it more likely to produce cracks at the grain boundaries. The prepared silicon-aluminum alloy is more susceptible to corrosion.
[0082] Experimental Example 4
[0083] The density of silicon aluminum alloy was measured by KW-300A aluminum alloy density measuring instrument; the corrosion performance test of silicon aluminum alloy was carried out by salt spray test simulating marine environment; 2.5% sodium chloride solution was evenly sprayed on the surface of silicon aluminum alloy sample for 96 hours, and after the experiment, the corrosion potential and corrosion rate of silicon aluminum alloy sample were tested by CHI660E electrochemical workstation; the corrosion rate calculation formula is: Where υ is the corrosion rate, m0 is the mass of the silicon-aluminum alloy sample before corrosion, m1 is the mass of the silicon-aluminum alloy sample after corrosion, S is the surface area of the silicon-aluminum alloy sample, and t is the corrosion time; the test results are shown in Table 6.
[0084] Table 6 Corrosion resistance of silicon aluminum alloys prepared in Examples 16-20 and Comparative Examples 7-8
[0085]
[0086] According to the data in Table 6, the density, corrosion potential and corrosion rate of Examples 16-20, Comparative Examples 7 and 8 were tested. The test results show that the density of the silicon aluminum alloys prepared in Examples 16-20 is greater than 2.60 g / cm 3 The corrosion potentials are all less than -0.80 V, and the corrosion rates are all less than 26.0 μm / a. Therefore, the silicon aluminum alloys prepared in Examples 16-20 have good corrosion resistance. This is because the added slag-forming agent contains 80% NaCl and 20% Na3AlF6. Na3AlF6 undergoes a decomposition reaction at high temperature, and the generated active substances such as fluoride ions can react chemically with the impurity elements in the alloy to form stable compounds. In addition, the addition of NaCl and Na3AlF6 can lower the melting point of the liquid silicon aluminum alloy, so that the alloy can maintain good fluidity at a lower temperature, thereby reducing the casting temperature, reducing energy consumption and damage to equipment caused by high temperature; it can also further reduce the direct contact between the alloy and the air, thereby reducing the oxidation rate of the alloy under high temperature conditions and improving its corrosion resistance; the negative pressure vacuum casting method can discharge the gas before the liquid alloy solidifies, thereby reducing the formation of pores and improving the density and quality of the casting; at the same time, it can reduce the oxidation and air entrainment of the liquid alloy during the filling process; under negative pressure, the chance of air contacting the liquid alloy is reduced, reducing the probability of oxidation on the alloy surface and further improving its corrosion resistance. After the slag-forming agent added in Comparative Example 7 is changed to calcium oxide, under high temperature conditions, calcium oxide will react with main components such as silicon and aluminum in the silicon-aluminum alloy to generate impurities, which is not conducive to the further reaction and will cause the corrosion resistance of the silicon-aluminum alloy to fail to achieve the expected effect; secondly, calcium oxide has a high melting point. After being added to the liquid silicon-aluminum alloy, the alloy temperature drops too fast due to heat absorption, affecting the fluidity of the alloy and further affecting the filling capacity during the casting process; furthermore, since the slag phase formed by calcium oxide has poor fluidity, in the subsequent slag removal process, the slag phase will adhere to the surface of the liquid alloy, increasing the difficulty of removing the slag phase, adversely affecting the quality of the silicon-aluminum alloy, and further reducing its corrosion resistance. Comparative Example 8 does not adopt the negative pressure vacuum casting method, but adopts the sand mold gravity casting method. The filling process is simple and rough, making the fluidity of the liquid silicon aluminum alloy difficult to control; at the same time, the liquid alloy is in direct contact with the sand mold, and the surface roughness of the sand mold will affect the surface quality of the casting. After the alloy solidifies, the surface of the casting will have the texture of the sand mold, resulting in a rough surface, which is not conducive to improving the corrosion resistance of the silicon aluminum alloy.
[0087] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A production method for preparing silicon aluminum alloy using coal gangue and fly ash, characterized in that: The production method is as follows: Mixing coal gangue powder and fly ash powder to obtain mixture A; and then fully mixing mixture A with wet charcoal powder to obtain mixture B; The mixture B is granulated to obtain a material; the material is fed into a distribution system to be evenly distributed to obtain a block material; The block material and the reducing agent are subjected to a heating and impurity removal treatment on a belt pre-reducing machine to obtain material A; the material A is screened for a second time to obtain material B; The material B is mixed with coal particles and then roasted at high temperature to obtain liquid silicon-aluminum alloy; the liquid silicon-aluminum alloy is allowed to stand for cooling, subjected to negative pressure vacuum casting, shaping, cooling, demoulding, cutting, cleaning and correction, and fine processing to obtain the silicon-aluminum alloy.
2. The method for preparing silicon aluminum alloy by using coal gangue and fly ash according to claim 1, characterized in that: The production method of the mixture A is as follows: respectively grinding coal gangue, fly ash and charcoal with a Raymond mill to make the particle size of the mixture 80-100 meshes to obtain the coal gangue powder, the fly ash powder and the charcoal powder; feeding the coal gangue powder and the fly ash powder into a double-helix conical mixer at a mass ratio of 35-55:25-45, adjusting the rotation speed of the double-helix conical mixer to 30-60r / min, mixing for 15 minutes, controlling the material filling rate in the double-helix conical mixer to 70%, and performing a thorough mixing to obtain the mixture A.
3. The method for preparing silicon aluminum alloy by using coal gangue and fly ash according to claim 1, characterized in that: The production method of the mixture B is as follows: 8-12 parts of charcoal powder and 3 parts of distilled water are pre-mixed to obtain the wet charcoal powder, and the mixture A, the wet charcoal powder and 10 parts of the distilled water are added into a spiral stirrer for secondary humidification and fully mixed to obtain the mixture B.
4. The method for preparing silicon aluminum alloy by using coal gangue and fly ash according to claim 1, characterized in that: The block production method is as follows: the mixture B is sent to a twin-screw extruder granulator with a pressure of 80-100 MPa and a feed rate of 10 kg / h and 5 parts of graphite lubricant are added to granulate to obtain the material; the granulation particle size of the twin-screw extruder granulator is controlled within the range of 3-5 mm.
5. The method for preparing silicon aluminum alloy by using coal gangue and fly ash according to claim 1, characterized in that: The block material production method comprises: feeding the material into the distribution system to distribute the material evenly to obtain the block material; the distribution system adopts a shuttle distributor, the running speed of the shuttle distributor is 3m / min, the end point residence time is 10s, and the material flow rate is 10-15m 3 / h, the height between the discharge port and the fabric plane is 1.0m.
6. The method for preparing silicon aluminum alloy by using coal gangue and fly ash according to claim 1, characterized in that: The production method of material A is as follows: the block material is gradually heated to 1150-1250°C on the belt pre-reduction machine and maintained for 18-25 minutes; the air flow velocity of the wind system is adjusted to 10m / s and the air flow rate is 20m 3 / min, so that the block material forms the material A with uniform thickness on the belt pre-reduction machine; the air flow direction of the wind system is opposite to the conveying direction of the block material.
7. The method for preparing silicon aluminum alloy by using coal gangue and fly ash according to claim 1, characterized in that: The production method of the liquid silicon-aluminum alloy is as follows: the material A is subjected to secondary screening through a vibrating circular screen to obtain the material B; the material B is mixed with coal particles in a mass ratio of 4:1 and sent to the silo of a silicon-aluminum-iron alloy furnace, and is subjected to high-temperature roasting at 2100-2150°C for a sufficient reduction reaction, and the liquid silicon-aluminum alloy is obtained after roasting for 2.3-2.5 hours; the mesh aperture of the vibrating circular screen is 1.0 mm; and the moving speed of the material A on the mesh is 0.2 m / s.
8. The method for preparing silicon aluminum alloy by using coal gangue and fly ash according to claim 1, characterized in that: The production method of the silicon-aluminum alloy is as follows: the liquid silicon-aluminum alloy is flowed into a ladle, and 2 parts of slag-forming agent are added into the ladle for purification and impurity removal; the liquid silicon-aluminum alloy is allowed to stand in the ladle for 13-15 minutes, and the temperature is reduced to 1450-1500°C and cast by a vacuum pressure casting machine; after shaping, the alloy is cooled, demoulded, and the surface is cleaned, the size is corrected, and fine-processed to obtain the silicon-aluminum alloy; wherein the slag-forming agent contains 80% of NaCl and 20% of Na3AlF6.
9. The method for preparing silicon aluminum alloy by using coal gangue and fly ash according to claim 8, characterized in that: The casting is as follows: placing the prefabricated mold into the vacuum pressure casting machine, controlling the negative pressure value of the vacuum pressure casting machine to be stable at 170-180hpa, and then pouring the liquid silicon aluminum alloy into the mold through a gate system and waiting for shaping.
Citation Information
Patent Citations
A high-performance silicon-aluminum alloy and its preparation method
CN109487129B
Cast aluminum-silicon alloys and their preparation methods, and aluminum-silicon alloys for aerospace or automotive castings.
CN115044809B
Process of refining aluminium silicon alloy from coal gangue or flyash
CN100999790A
Process for extracting silicon-aluminum alloy from fly ash
CN104419829A
Method for preparing ferrosilicon aluminum alloy through carbon thermal reduction of fly ash
CN109536727A